Renal mitochondrial restoration by gymnemic acid in gentamicin-mediated experimental nephrotoxicity: evidence from serum, kidney and histopathological alterations - Gumbar, Shubhangi; Bhardwaj, Sudeep; Mehan, Sidharth; Khan, Zuber; Narula, Acharan S.; Kalfin, Reni; Tabrez, Shams; Zughaibi, Torki A.; Wasi, Samina (Frontiers in Pharmacology, 2023)
Background Nephrotoxicity refers to the toxigenic impact of compounds and medications on kidney function.There are a variety of drug formulations, and some medicines may affect renal function in multiple ways. Nephrotoxins are substances that are harmful to the kidneys. Purpose This investigation examines the renoprotective effect of gymnemic acid (GA) on Wistar rats with gentamicin-induced nephrotoxicity by analyzing serum, kidney, and histopathological markers. Study-design/ Methods The current study investigated the protective effect of GA at doses of 20, 40, and 60 mg/kg against gentamicin-induced nephrotoxicity in rats. Vitamin E was administered to compare the antioxidant capacity and efficacy of GA. In addition to the treatment groups, 100 mg/kg of gentamicin was administered intraperitoneal for 14 days. At the end of the study protocol, kidney homogenate, blood, and serum were evaluated biochemically. Serum creatinine, blood urea, glomerulus filtration rate (GFR), mitochondrial dysfunctions, inflammatory cytokines, and renal oxidative stress were examined to assess gentamicin-induced nephrotoxicity. The impact of GA on the kidney was confirmed by further histological analysis. Results This study establishes a correlation between antibiotic use, specifically aminoglycosides, and acute renal failure. The research demonstrates the nephrotoxic effects of aminoglycosides, inducing mitochondrial ETC-complex dysfunction, and renal tissue inflammation in experimental rats. . GA's antioxidant properties restored renal oxidative stress markers, reducing kidney inflammation and injury. Histopathological analysis revealed a significant reduction in renal injury with GA treatment. Additionally, GA demonstrated greater efficacy than Vitamin E in restoring antioxidant potential and mitochondrial enzymes. Conclusion Consequently, our findings imply that long-term use of GA may be a suitable therapeutic strategy for reducing aminoglycoside toxicity, such as gentamicin-induced nephrotoxicity. The current study suggests GA's potential in treating gentamicin-induced nephrotoxicity and acute renal failure, meriting further investigation using advanced techniques.